Simple synthesis of multi-halogenated alkenes from 2-bromo-2-chloro-1,1,1-trifluoroethane (halothane) - Karuo, Yukiko; Tarui, Atsushi; Sato, Kazuyuki; Kawai, Kentaro; Omote, Masaaki (Beilstein Journal of Organic Chemistry, 2022)
A series of aryl fluoroalkenyl ethers that contain chlorine and bromine as well as fluorine atoms were prepared in moderate to good yields via the reactions of phenols and 2-bromo-2-chloro-1,1,1-trifluoroethane (halothane) in the presence of KOH. This simple reaction enabled the construction of highly halogenated compounds with the potential for further functionalization. The reaction involved a highly reactive difluoroethylene intermediate, which was produced by the reaction between halothane and KOH.
Keywords: aryl 1-monofluorovinyl ether; electrophilic 1,1-difluoroethene; halothane; multi-halogenated alkene; phenol